2020
DOI: 10.1002/bmb.21334
|View full text |Cite
|
Sign up to set email alerts
|

Drawing in 3D: Using 3D printer pens to draw chemical models

Abstract: Development of three-dimensional (3D) printing technology has started a new chapter for in-classroom modeling of chemical molecules. The technology provides the opportunity to design and produce various types of personalized models.However, using classical 3D printers is time consuming, and it is hard to involve students in the modeling process during traditional class times. One solution can be using hand-held 3D printers (3D pens) that allow users to instantly draw geometrical structures. Unfortunately, draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…(de Cataldo et al, 2018). Bernard & Mendez (2019) suggested the use of pen-like 3D writing products called "Handheld 3D Printer" or "3D Pen" in creating geometric structures, considering the long product acquisition time in conventional 3D printers and therefore very difficult to integrate into the course period. However, they stated that these pen-like products should be supported with templates created with classical 3D printers because it is difficult to make 3D drawings directly.…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…(de Cataldo et al, 2018). Bernard & Mendez (2019) suggested the use of pen-like 3D writing products called "Handheld 3D Printer" or "3D Pen" in creating geometric structures, considering the long product acquisition time in conventional 3D printers and therefore very difficult to integrate into the course period. However, they stated that these pen-like products should be supported with templates created with classical 3D printers because it is difficult to make 3D drawings directly.…”
Section: Figure 12mentioning
confidence: 99%
“…Figure 19 illustrates the use of the thus generated template for the toluene molecular model. (Bernard & Mendez, 2019).…”
Section: Figure 12mentioning
confidence: 99%
“…The rates were calculated using the equations derived from Azimi et al ( 2016), as shown in Equation (1). 7 The total L UFP was calculated using the concentration from the final decay period after completion of the operation, as shown in Equation (2).…”
Section: Calculation and Statistical Analysismentioning
confidence: 99%
“…Unlike a 3D-printer, the extruder nozzle of a 3D-pen is moved manually by the user and the ventilator, cooling system, and software in a 3D-printer are removed for portability. 1,2 Since 3D-pens are portable and easier to operate than 3D-printers, their use by children is increasing. From 2013, the annual growth rate of the global 3D-printing market was 25.9% and the market value is projected to reach 18 billion USD by the end of 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation